2022
DOI: 10.1111/jace.18642
|View full text |Cite
|
Sign up to set email alerts
|

Phase equilibria of MgO–Al2O3–TiO2 system at 1600°C in air: Emphasis on pseudobrookite and spinel solid solution phases

Abstract: The recycling of titanium from titania‐bearing slag is an important part of the circular economy; however, the yield of titania is restricted due to the lack of fundamental thermodynamic data. In the present work, the equilibrium phase relations of MgO–Al2O3–TiO2 system in air at 1600°C have been determined using a high‐temperature equilibration‐quenching technique followed by X‐ray photoelectron spectroscopy, scanning electron microscopy‐energy‐dispersive X‐ray spectrometry, and X‐ray diffraction. Ti4+ was co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(1 citation statement)
references
References 63 publications
0
1
0
Order By: Relevance
“…It was reported that when the Ti content in steel is sufficiently high (e.g., w(Ti) > 0.1%), and/or the oxygen partial pressure is sufficiently low, Ti primarily exists in the form of Ti 2 O 3 . [28,29] In this study, due to the low oxygen potential, the oxide of TiO x in the reacted layer is treated as Ti 2 O 3 during the composition calculations of EDS results. In fact, this treatment cannot change the variation trend of the TiO x in the layers, and the valence of the Ti ions in the oxide may still need further confirmation.…”
Section: Mgo Refractorymentioning
confidence: 99%
“…It was reported that when the Ti content in steel is sufficiently high (e.g., w(Ti) > 0.1%), and/or the oxygen partial pressure is sufficiently low, Ti primarily exists in the form of Ti 2 O 3 . [28,29] In this study, due to the low oxygen potential, the oxide of TiO x in the reacted layer is treated as Ti 2 O 3 during the composition calculations of EDS results. In fact, this treatment cannot change the variation trend of the TiO x in the layers, and the valence of the Ti ions in the oxide may still need further confirmation.…”
Section: Mgo Refractorymentioning
confidence: 99%